2017
DOI: 10.1111/rda.12988
|View full text |Cite
|
Sign up to set email alerts
|

Extended day length in late winter/early spring, with a return to natural day length of shorter duration, increased plasma testosterone and sexual performance in rams with or without melatonin implants

Abstract: Sixteen rams were used to quantify the effects of long days, imposed during late winter/early spring, with or without exogenous melatonin, on plasma testosterone concentrations and ram serving capacity. Rams were assigned to two groups: photoperiod-treated rams (Artificial Photoperiod, AP; n = 8), exposed to 2 months of long days (16 hr of light/day) between 22 December and 22 February, and control rams (Natural Photoperiod, NP; n = 8). At the end of the long-day period, AP rams were returned to the natural ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
(42 reference statements)
1
10
0
1
Order By: Relevance
“…These findings support past research as melatonin treatment and photoperiodic effects were also associated with improvements in ram reproductive performance in Rasa Aragonesa rams, and earlier onset of puberty in Rasa Aragonesa ewe lambs [ 12 , 21 ]. The reduction in the age at which first lambing occurred, as observed in this study, is also comparable to that found in previous experiments with melatonin-treated Sarda ewe lambs [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…These findings support past research as melatonin treatment and photoperiodic effects were also associated with improvements in ram reproductive performance in Rasa Aragonesa rams, and earlier onset of puberty in Rasa Aragonesa ewe lambs [ 12 , 21 ]. The reduction in the age at which first lambing occurred, as observed in this study, is also comparable to that found in previous experiments with melatonin-treated Sarda ewe lambs [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…6G ). Under normal conditions, the levels of blood testosterone in rams varies considerably ( 34 36 ). Hence, we measured the levels of testosterone in each BTV-1-infected ram at day 5, and late at days 8 to 11 or day 15, relative to the levels found in the same rams at day 0 before infection (taken as 100).…”
Section: Resultsmentioning
confidence: 99%
“…Although sexual-performance tests were not performed in this experiment to avoid the effect of previous contact with females on sexual activity, especially in the control rams, our previous studies have confirmed that light-treated rams exhibit higher sexual behavioral expression [14] than do rams kept under the natural seasonal photoperiod, and have high plasma testosterone concentrations in spring [6,7,14]. It has been found [15] that the proportion of ewes that ovulated was highest in groups that had been exposed to rams that exhibited intense, rather than moderate, sexual behavior, and concluded that, in addition to a pheromone signal, the sexual intensity of the ram is important in initiating ovarian cycles.…”
Section: Resultsmentioning
confidence: 92%